Design Analysis of Microstrip Rectangular Patch Array Antenna 16×1 on X-band Radar (Jurnal Elektronika dan Telekomunikasi, 2019)
Radar has been widely used for various purposes such as monitoring atmospheric precipitation. For that purpose, it gives more accurate results than satellites do. Previous research has developed navigation radar that alters its functions into an atmospheric precipitation monitoring radar. To improve the development of the radar, an antenna system will be developed in this research. The purpose of developing this antenna is to obtain better data reception results. This antenna is a microstrip rectangular array antenna that works on X-band with a frequency of 9.41 GHz. Microstrip antenna is chosen since it has several advantages such as small dimensions and relatively low costs. The designed antenna gain ≥ 12 dB, bandwidth of 60 MHz, and horizontal polarization. Antenna fabrication produces a microstrip rectangular 16 x 1 array antenna using the mitered bend method at a frequency of 9.4 GHz with a reflection coefficient of -22.8 dB, VSWR of 1.2, gain of 13.21 dB, unidirectional radiation patterns and horizontal polarization.